Social consequences of COVID-19 in a low resource setting in Sierra Leone, West Africa. (August 2020) - Buonsenso, Danilo; Cinicola, Bianca; Raffaelli, Francesca; Sollena, Pietro; Iodice, Francesco
Highlights: COVID-19 is increasingly reported in Sierra Leone. Most people of a poor village in Sierra Leone lost their jobs, as a consequence of COVID-19 lockdown. Most people of a poor village in Sierra Leone have difficulties in providing food for their families. Abstract: Economical and psychological consequences of the lockdown in low-resource setting in rural Africa are unknown. We drafted a survey in order to address the social impact of COVID-19 lockdown on a rural village in Sierra Leone. The survey developed by the study group and translated in the local language, distributed to the householders of the village on April 13th and responses collected on April 14th, when Sierra Leone was on day 11 of lockdown. The questions aimed to assess in the community the following items: age group, main activities before lockdown, change in income and ability to feed the family during lockdown, anxiety during lockdown. 78 householders (100% of Bureh Town) replied. All, expect one, declared a 51−80% (19.2%) to 81−100% (79.4%) reduction of weekly income compared with the pre-lockdown period, declaring difficulties in providing food for the family members (82%), and anxiety (60%). Our analyses showed that people lost their jobs and have difficulties in providing food for their families. Highlights : Our analyses in a low resource setting in rural Africa in Sierra Leone, West Africa, showed that people lost their jobs and have difficulties in providing food for their families, as a consequence of COVID-19 lockdown